The battle for the Falklands - Hastings, Max.; Jenkins, Simon (New York : W.W. Norton & Company, 1983)
A combination of on-the-spot reporting and an analysis of the political and diplomatic developments traces the curious course and far-reaching effects of the Falkland Islands War.
Forgotten Islands -- The Seventeen Years' War -- Galtieri's Gamble -- The Admiral's Hour -- Task Force -- Haig's Doves -- Ascension to South Georgia -- Failure of a Mission -- A War at Sea -- Clearing the Decks -- Operation Sutton -- San Carlos -- Goose Green -- The Politics of the Land War -- Triumph on Kent, Tragedy at Fitzroy -- The Battle for the Mountains -- Aftermath -- The Falkland Islands Task Force -- The Falklands Honours List -- The Franks Report -- The Falkland Islands -- The Task Force Sails -- The Total Maritime Exclusion Zones -- The Landing at Port San Carlos -- The Two-Pronged Attack towards Port Stanley -- The Battle for Goose Green -- The Battle for Stanley.
Includes bibliographical references and index.
Keywords: 1982; Falkland Islands War, 1982.; Guerre des Malouines, 1982.; Falklandkrieg; Falkland-oorlog.; Falkland Islands War, 1982.